A QoS Aware Cluster Head Selection and Hybrid Cryptography Routing Protocol for Enhancing Efficiency and Security of VANETs - JUBAIR, MOHAMMED AHMED; A. MOSTAFA, SALAMA; DZEBARI, DILOVAN ASAAD; MUHEE HARIZ, HUSSEIN; ABDULSATTAR, NEJOOD FAISAL; HASSAN, MUSTAFA HAMID; ABBAS, ALI HASHIM; HASHIM ABBAS, FATIMA; ALASIRY, AREEJ; ALOUANE, M. TURKI-HADJ (IEEE, 2023)
Nowadays, VANET (Vehicular Ad hoc Network) is one of the key aspects of developing advanced intelligent transportation systems. Due to its huge mobility and rapid topology alteration, the network exposes to link failure that affects the firmness of the network and causes delay and congestion. Additionally, the dynamic change in the network routing affects the network’s security, making it vulnerable to various attacks, and results data loss. An efficient and highly secured routing protocol is needed to overcome these drawbacks. Subsequently, this research proposes a new routing protocol that combines the Quality of Service (QoS)-aware Cluster Head (CH) selection and hybrid cryptography named QoS+. The QoS+ protocol is mainly divided into QoS-based CH selection and hybrid cryptography modules. The CH selection module based on QoS parameters attempts to provide reliable and stable clusters and improve the firmness and connectivity during the communication process of the network. The hybrid cryptography module contains Advanced Encryption Standard (AES) and Elliptic Curve Cryptosystems (ECC) algorithms. It attempts to improve the security and privacy of the network. The QoS+ protocol is evaluated by a developed VANET simulator using NS2 software. The simulator consists of a network model, a load model, and an attack model. Various speed and transmission ranges and gray hole and wormhole attacks are used in the simulator. The outcome calculated from the performance analysis shows that the proposed QoS+ protocol has a 7% to 24% higher message success rate, 500 to 800 higher packets normalized routing load, 350 to 550 Kbps higher throughput, 5% to 17% higher efficiency, and 50ms to 12ms lower end-to-end delay when compared with the earlier works of ECHS and KMSUNET. The proposed QoS+ protocol also achieves superior performance in terms of CH efficiency, cluster member efficiency, and average cluster number with various speeds and transmission ranges.